Content of Pro- and Anti-inflammatory Cytokines in Blood Serum of Children with Bronchial Asthma of Various Severity - O.I. Smiyan; V.O. Kurganska; O.P. Moshchych; P.I. Sichnenko; V.A. Gorbas (Zaslavsky O.Yu., 2012)
The paper presents the findings of investigation of content of proinflammatory interleukin-1 and anti-inflammatory interleukin-4 in blood serum of children with asthma in the dynamics of disease and dependence of their level on severity of illness. Determination of these cytokines concentration was carried out in 86 children aged from 13 to 18 years. Comparison group consisted of 20 relatively healthy children of appropriate age and gender. We have established a significant increase of both cytokines level in blood serum, which was most pronounced in acute bronchial asthma, but remained high after standard treatment and remission achieved by patients. There have been define the dependence of disorders on the severity of the disease.